Analytical model for critical corrosion level of reinforcements to cause the cracking of concrete cover. (30th October 2019) - Zhang, Kaijian; Xiao, Jianzhuang; Zhao, Yuxi; Zhang, Qingtian
Highlights: Plastic properties of concrete were considered in calculating expansive pressures. Strain softening of concrete was modeled to obtain accurate concrete displacement. A proposed model was validated by corrosion tests of reinforcements in concrete. Abstract: This paper proposes an analytical model to calculate the critical corrosion level of reinforcements embedded in the concrete. The porous zone, the plasticity and strain softening of concrete were considered. The proposed model was verified by the simulation and test results, and the test validation shows that the predicted critical corrosion level of reinforcements for both natural aggregate concrete (NAC) and recycled aggregate concrete (RAC) based on the proposed model has a relative error lower than 5.0% compared with the test result when the replacement ratio of recycled aggregates is lower than 33.3%. It concludes that the proposed model can be applied to the prediction of the critical corrosion level of reinforcements in both NAC and RAC, and further the analysis of durability of concrete structures.